Editorial - Sturrock, Peter (Journal of Scientific Exploration, 2010)
I see we have something for almost everyone in this issue–something, at least, for readers with any interest in ufology, psi phenomena, past-life memories, or ‘‘altered states of consciousness.’’ We are also adding something new.